2019
DOI: 10.3390/su12010294
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Assessment of Campus Buildings Based on a Life Cycle Assessment–Life Cycle Cost Integrated Model

Abstract: The development of higher education has led to an increasing demand for campus buildings. To promote the sustainable development of campus buildings, this paper combines social willingness-to-pay (WTP) with the analytic hierarchy process (AHP) based on the characteristics of Chinese campus buildings to establish a life cycle assessment–life cycle cost (LCA–LCC) integrated model. Based on this model, this paper analyses the teaching building at a university in North China. The results show that the environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…To begin with, manual calculations are carried out by utilizing Inventory of Carbon and Energy (ICE) database and software computation carried out using One Click LCA, considering GaBi and ecoinvent databases [26][27][28]. One Click LCA is trailed by EPDs given the ISO 14040 and EN 15804 standards [29]. The present study investigates the carbon footprint of structures with four phases of the LCA.…”
Section: System Boundaries and Functional Unitmentioning
confidence: 99%
“…To begin with, manual calculations are carried out by utilizing Inventory of Carbon and Energy (ICE) database and software computation carried out using One Click LCA, considering GaBi and ecoinvent databases [26][27][28]. One Click LCA is trailed by EPDs given the ISO 14040 and EN 15804 standards [29]. The present study investigates the carbon footprint of structures with four phases of the LCA.…”
Section: System Boundaries and Functional Unitmentioning
confidence: 99%
“…4 compares the values obtained in this study and those found in the literature review published by Röck et al (2020a, b). For laboratory and research building typology, only Georges et al (2015) have provided information for the technical and electrical equipment, while other studies have limited the system boundary to the building fabric (Wu et al 2012;Azari 2014;Kofoworola and Gheewala 2008;Asdrubali et al 2013;Xie et al 2018;Wang et al 2018;Biswas 2014;Azzouz et al 2017;Attia 2016;Eberhardt et al 2019). Based on the energy reference area, the KBOB ( 2016) database also provides simplified information for the impacts of electrical equipment.…”
Section: Resultsmentioning
confidence: 99%
“…(2020) and Hoxha et al (2020a), LCAs of university buildings are usually limited to the building fabric, namely, the structural materials, cladding, insulation, and main finishes (Wu et al 2012;Azari 2014;Kofoworola and Gheewala 2008;Asdrubali et al 2013;Xie et al 2018;Wang et al 2018;Biswas 2014;Azzouz et al 2017;Attia 2016;Eberhardt et al 2019), or even just to major materials consumed (Chang et al 2019), and often not covering all life cycle stages (Varun Sharma et al 2012;Xue et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The expense names and cost components in Figure 2 and Figure 3 take the "Budget Compilation and Calculation Standards of Grid Construction" issued in 2013 by the National Energy Administration as reference. Because the research content of the life cycle cost is based on time series, the cost of the project's life cycle is decomposed and estimated, and then the results of each stage are analyzed [41]. Therefore, this paper divides and models the life cycle cost according to its chronological order of costs and expenses to reflect the changes and connections among the various stages of the project's life cycle.…”
Section: Lcc-cld Modulementioning
confidence: 99%